EffectOf Panax Ginseng Extract For The Increased Number Of Fibroblasts Cells After Tooth Extraction - Rizky Hutomo, Ferdian; Permatasari, Nur; Andari Wulan, Kartika (Universitas Muhammadiyah Yogyakarta, 2012)
The process of tooth extraction can lead to injury. One of the factors that influencethe process of wound healing after tooth extraction is the number of fibroblastcells. The content of saponins can increase the number of fibroblasts cells aftertooth extraction. Asian ginseng plants known to contain saponins (ginsenoside).The purpose of this study was to determine the effect of Asian ginseng extract(Panax ginseng extract) for the increased number of fibroblasts cells after toothextraction. The research method used is in vivo experimental design with thedesign methods Randomized Post Test Only Control Group Design. In this studyused twentty male rattus novergicus and divided into four group, consisting ofcontrol group (K1) were not given Asian ginseng extract, treatment groupsnumber one (K2) were given 25mg/Rattus novergicus/day doses of Asianginseng, treatment groups number two (K3) were given 50mg/ Rattusnovergicus/day doses of Asian ginseng, and treatment groups number three (K4)were given 75mg/Rattus novergicus/day doses of Asian ginseng. Histopathologicpreparations used for counting the number of fibroblasts cells. The results ofstatistical tests indicate there are differences in the number of fibroblast cells inRattus novergicus between the four different groups (ANOVA, p 0.05) and thereis a very strong correlation between increasing doses of ginseng extract with anumber of fibroblast cells in Rattus novergicus tooth socket (Pearson, R = 0.915 p0.05). The conclusion of this study is Asian ginseng extract can increase thenumber of fibroblasts in the tooth socket after tooth extraction, it is recommendedthat research about the amount of saponin in Asian Ginseng extract